Lupus anticoagulant-hypoprothrombinemia syndrome and catastrophic antiphospholipid syndrome in a patient with antidomain I antibodies. Issue 5 (July 2016) - Galland, Joris; Mohamed, Shirine; Revuz, Sabine; de Maistre, Emmanuel; de Laat, Bas; Marie, Pierre-Yves; Zuily, Stéphane; Lévy, Bruno; Regnault, Véronique; Wahl, Denis
Abstract : Lupus anticoagulant-hypoprothrombinemia syndrome is a rare condition characterized by the association of acquired factor II deficiency and lupus anticoagulant. Contrary to classical antiphospholipid syndrome, it may cause severe life-threatening bleeding (89% of published cases). We report a patient, positive for antidomain I antibodies, with initially primary lupus anticoagulant-hypoprothrombinemia syndrome without previous clinical manifestation or underlying systemic disease. Five years later, he experienced the first systemic lupus erythematous flare. Within a few days, catastrophic antiphospholipid syndrome was diagnosed with heart, liver and kidney involvement. The patient recovered under pulse steroids, intravenous heparin and intravenous immunoglobulins.